Grundtvigianisme og pietisme : Et Kalkar-brev - Hansen, C. Rise (Kirkehistoriske Samlinger, 1988)
Skat Rørdam was known to be a clever tutor of theology, and in 1862 the Danish Missionary Society appointed him the principal of its mission school in Copenhagen. The relationship was strained between him and his five pupils, none of whom were particularly young, nor were any of them academically trained. It was Skat Rørdam’s opinion that his pupils were influenced by two forms of Herrnhuter pietism, which would in his view be considered sectarian by Lutheran congregations. And for this reason, Skat Rørdam wanted to resign from his post as leader of the mission school. On a visit to the school on 23. June 1863, the then chairman of the Missionary Society, Dr. C. A. H. Kalkar, found Skat Rørdam in the act of writing his letter of resignation. This caused Dr. Kalkar deep regret, and he wrote the letter shown here to his close friend, Dr. Hans Christian Rørdam, former chairman of the Society and the father of Skat Rørdam. In his letter he does not wholly share Skat Rørdam’s views on pietism, and he tries to mediate between teacher and pupils but without result. Thus at his own request, Skat Rørdam was relieved of his post, to continue with greater success the tutoring of theological students, although he never entirely relinquished his interest in the foreign missions.